PENGATURAN LAMPU LALU LINTAS MENGGUNAKAN PENDEKATAN SISTEM PAKAR - Muhammad Izman Herdiansyah; Linda Atika (Jurnal Ilmiah Matrik, 2016)
This study aimed to analyze the factors that cause the occurrence of traffic congestion in some urban and solve it by using an expert system. Sistem serves to record and duplicate the capabilities of experts. Expert systems in this study was built within the framework of network optimization designed to solve the problem of traffic congestion in urban areas. Control of traffic jams and optimal well not be possible without the use of intelligent data management system and realtime. In this study, we were able to improve the quality of congestion control in both the strategic aspects as well as operasional. This Research using survey methods, and development models. The results of the study are: a) traffic management policy input and control traffic congestion of Dishubkominfo Palembang and municipal police; and b) the optimization model and control traffic congestion at the intersection; c) the data processing for controlling the traffic congestion that can be implemented to overcome congestion in some urban areas.